STUDI LITERATUR MENGUATKAN IDENTITAS BUDAYA GENERASI Z MELALUI BK MULTIKULTURAL DI ERA GLOBALISASI - Shafira Devi Puspitasari; Veni Meisya Putri; Sabrina Azis Azzahroh; Arindra Pasca Mauliddiana; Kiki Katrin Trisya Ramadhani; Ari Khusumadewi; Ela Nur Fadilah (Program Studi Bimbingan dan Konseling, Universitas Negeri Jakarta, 2026)
Developments in information and communication technology have accelerated the process of cultural globalization, allowing various popular cultures from abroad to easily enter and influence the lives of the younger generation. One phenomenon that has attracted much attention is the increasing interest in Korean culture (K-Pop) among Generation Z in Indonesia through various social media platforms such as TikTok, Instagram, and YouTube. This phenomenon not only influences entertainment choices but also impacts the lifestyle, thinking, and views of the younger generation towards local culture. This study aims to analyze the impact of K-Pop culture on Generation Z and explore the role of multicultural guidance and counseling in strengthening local cultural identity amidst the current of globalization. The method used in this study is a qualitative descriptive approach with literature study techniques and content analysis from various sources such as journals, books, scientific articles, and digital content. The results of the analysis show that K-Pop culture has positive impacts such as increased motivation, broadening global horizons, and becoming a source of inspiration for teenagers. However, this impact can also have negative effects such as consumptive behavior, excessive fanaticism, and a tendency to decline in interest in local culture. Therefore, appropriate initiatives through multicultural education, guidance, and counseling are needed to help the younger generation understand cultural diversity and raise awareness of preserving local cultures amidst global cultural developments.